Demulsification of Water-in-Crude Oil Emulsion via Conventional Heating and Microwave Heating Technology in their Optimum Conditions - Akbari, Sweeta; Nour, A. H.; Saidatul Shima, Jamari; Rajabi, Abdul Qayom (AENSI Publishing, 2016)
A serious problem during the production and refinery process of crude oil is the existence of emulsified water in the crude oil. From the economic and environmental points of view, water must be removed from the crude oil before going for further processing. In the last two decades, several demulsification techniques have been applied by many researchers. Since, the best method is based on the best water separation efficiency. Therefore, a comparative study between microwave heating and conventional heating demulsification in their optimum conditions has been carried out. Both methods were performed with the assistance of chemical demulsifier. Through the experimental results, it was found that comparing to the conventional heating; microwave dielectric heating earned the best separation efficiency (100 %) in a short time. The optimum condition in microwave dielectric heating was irradiation time (3 minutes), microwave power (360 watt), and 2.50 vol. % demulsifier concentration. However, in conventional heating using “hotplate” the highest separation efficiency (96 %) was obtained at 160 ºC, and heating time 5 minutes.